Contextual learning integrated with gamification: Effects on mathematical connection ability and learning motivation in ratio and proportion - Nurmiati Nurmiati; Endang Wahyuningrum; Sudirman Sudirman; Tán Lì Nà (International Journal of Mathematics and Sciences Education, 2026)
Mathematical connection ability remains a persistent weakness among Indonesian junior secondary students, with diagnostic data from SMP Negeri 2 Kaloran, Temanggung Regency, Indonesia showing that 74–81% of Grade 7 students failed to meet minimum competency on ratio and proportion across two academic years. Compounding this problem, classroom observations indicated chronically low learning motivation among the same cohort. This study examined whether contextual learning integrated with gamification (CTL+Gamification), delivered through the Wayground platform, could address both deficits simultaneously. A quasi-experimental design with nonequivalent control groups was employed, involving 56 Grade 7 students (experimental n = 27; control n = 29) selected through multi-stage cluster random sampling in Temanggung Regency. The experimental group received six sessions embedding ratio and proportion content in locally meaningful contexts, tobacco farming, coffee yield, and map scale, while the control group received conventional expository instruction. Mathematical connection ability was assessed using a validated seven-item essay test (Aiken’s V = 0.83; α = 0.84), and learning motivation using a 25-item ARCS-based questionnaire (α = 0.87). Independent-sample t-tests and two-way ANOVA revealed that the experimental group significantly outperformed the control group in mathematical connection ability (t = 3.542, p = .001, d = 0.97) and learning motivation (t = 2.201, p = .032, d = 0.59), while the instructional model × motivational level interaction was nonsignificant (F = 1.306, p = .280). These findings suggest that contextually grounded, gamified instruction can strengthen both cognitive and affective outcomes, offering a locally adaptable model for mathematics teaching under Kurikulum Merdeka.